Incidence and risk factors of mental disorders in the elderly: The European MentDis_ICF65+ study. (May 2022) - Andreas, Sylke; Schulz, Holger; Volkert, Jana; Lüdemann, Jonas; Dehoust, Maria; Sehner, Susanne; Suling, Anna; Wegscheider, Karl; Ausín, Berta; Canuto, Alessandra; Crawford, Michael J; Da Ronch, Chiara; et al.
Objective: While incidence rates of depression and anxiety disorders in the elderly have been comprehensively investigated, the incidence rates of other mental disorders have rarely been researched. The incidence rate and predictors of various mental disorders in the elderly were evaluated in different European and associated countries. Methods: A cross-sectional and longitudinal multi-centre survey of Diagnostic and Statistical Manual of Mental Disorders (4th ed.) diagnoses was conducted in different European and associated countries (Germany, Italy, Spain, Switzerland, the United Kingdom and Israel) to collect data on the prevalence and incidence of mental disorders in the elderly. The sample size of the longitudinal wave was N  = 2592 elderly. Results: The overall 1-year incidence rate for any mental disorder in the elderly is 8.65%. At 5.18%, any anxiety disorder had the highest incidence rate across all diagnostic groups. The incidence rate for any affective disorder was 2.97%. The lowest incidence rates were found for agoraphobia (1.37%) and panic disorder (1.30%). Risk factors for the development of any mental disorder were never having been married, no religious affiliation, a higher number of physical illnesses and a lower quality of life. Conclusion: In comparison to other studies, lower incidence rates for any affective disorder and middle-range incidence for any anxiety disorder were found. To the authors' knowledge, no prior studies have reported 1-year incidence rates for somatoform disorder, bipolar disorder and substance misuse in community-dwelling elderly. These findings indicate the need to raise awareness of psychosocial problems in the elderly and to ensure adequate availability of mental health services.